Pengaruh Inflasi, Nilai Tukar, dan Produk Domestik Bruto terhadap Indeks Harga Saham di Jakarta Islamic Index - Widyaningtias, Ayu; Mawaddah, Romdhonah Zahrotul; Amaroh, Siti (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
The purpose of this research is to find out whether inflation, exchange rates, and PDB affect the JII stock price index. This research method is quantitative. Data obtained from secondary data in the form of a time series of 32 samples. This study uses Eviews version 13 in data processing. The results of this study on the t test stated that inflation did not significantly affect the JII stock price index based on t count < t table (1.497416 <2.048407) and the number of probs. (0.1463 > 0.05). The exchange rate has no significant relationship to the JII index as shown by t count < t table (-5.675294 < 2.048407 and total prob. (0.000 < 0.05). Meanwhile, PDB has a significant effect on the JII stock price index from the t count > t table (5.628365 > 2.048407) and the number of probs (0.000 <0.05). Whereas in the simultaneous test the variables inflation, exchange rate, and PDB affect the JII stock price index as evidenced by f count > f table (12.511175 > 2.946685) and a significance level (0.000 <0.05).